2015
DOI: 10.7314/apjcp.2015.16.5.2013
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practice about Pap Smear Test among Women Living in Bojnourd, North East of Iran: a Population-Based Study

Abstract: Background: The aim of the study was to assess the extent of knowledge, attitudes and practical behavior of women in Bojnourd conerning the Pap smear test. Materials and Methods: This cross-sectional and populationbased study was conducted with 1000 Iranian women aged 15-60 years old in Bojnourd city. In order to collect the data, a validated questionnaire was provided in four sections covering demographic information and questions about knowledge, attitude and practice about the Pap smear. Statistical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…In the study of Keshavarz et al [26], husbands were reported as the most important sources of subjective norms. In addition, in a study by Bahri et al [8], 87.3% of women had positive attitudes toward the Pap smear test. A study performed on Taiwanese women showed that subjective norms were the predictors of intention of cervical cancer screening [27].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the study of Keshavarz et al [26], husbands were reported as the most important sources of subjective norms. In addition, in a study by Bahri et al [8], 87.3% of women had positive attitudes toward the Pap smear test. A study performed on Taiwanese women showed that subjective norms were the predictors of intention of cervical cancer screening [27].…”
Section: Discussionmentioning
confidence: 92%
“…The difference in cervical cancer mortality between developing and developed countries is directly related to the Pap smear test compliance. Thus, implementing programs to improve health-related behaviors, beliefs, and awareness regarding the Pap smear test is essential [8]. These programs can reduce the incidence of cervical cancer and its mortality up to 79% and 70%, respectively [9].…”
Section: Open Accessmentioning
confidence: 99%
“…In the other study among 1000 women aged between 15 to 60 years old in Bojnourd, 14.6% had very weak and 59.4% had weak knowledge toward the Pap smear test while most of the participant (87.3%) had a positive attitude toward the Pap smear test (12).…”
Section: Introductionmentioning
confidence: 85%
“…This part deals with and summarizes the study findings, addresses the interpretations, and discusses these findings in context with the existing literature. The results of this study shows that out of the 380 female employees more than half of them (55.3%) had an overall adequate knowledge.In contrast, findings of a cross-sectional study conducted among 1000 Iranian women, displayed that a large percentage of participants (59.4%) had weak knowledge; and only 7.9 % of women had good knowledge (Bahri, Jajvandian, Bolandhemmat, & Mirzaiinajmabadi, 2015).This contradiction of results in both studies might be due to the differences of participants' educational levels. The results showed that women aged between (50-60 years) had significantly less knowledge than women aged below 40 years old.…”
Section: Discussionmentioning
confidence: 79%